Evaluación de captación de carbono mediante cepas fúngicas y bacterianas en plantaciones de cacao nacional (Theobroma cacao L.) - Mero Vera, Karla Patricia (2024)
The purpose of this study was to evaluate carbon sequestration by fungal and bacterial strains in soils of national cocoa plantations Theobroma cacao L of the Escuela Superior Politécnica Agropecuaria de Manabí Manuel Félix López. In the study, four treatments were applied with the implementation of Trichoderma longibrachiatum (EM-72) for T1, Trichoderma reesei (EM-49) for T2, Bacillus subtilis (EM-54) for T3 and Bacillus licheniformis (EM-44) for T4, to identify significant differences between treatments, with respect to the variables under study, the completely randomized design (DCA) was applied, with the respective analysis of variance and comparison of means with the Tukey test at 5%. The results show a variability in the chemical parameters of the soil in response to the treatments applied, showing significant increases in the levels of ammonium, phosphorus and potassium, which are related to the neutrality of the pH. In addition, there was an unrepresentative increase in organic matter (8%) in relation to the initial parameters (7%), In terms of carbon sequestration, the treatments with Trichoderma longibrachiatum and reesei showed more significant results (p<0.0001**) compared to Bacillus subtilis and licheniformis, with Trichoderma longibrachiatum showing the best sequestration parameters over time with a mean sequestration of 28.75 to 15 mg*kg-s. The results suggest that the evaluated strains have the ability to contribute to carbon sequestration, allowing to improve the health and fertility of agricultural soils.